Impact of Taqwa (Islamic piety) on employee happiness: A study of Pakistan's banking sector - Raj Maham; Omar Khalid Bhatti (Cogent Business & Management, 2019)
The concept of "employee happiness" has received much research attention within the framework of Western values, but the equivalent concept has not been explored in the context of other cultures and religions, such as the Islamic context of Pakistan's banking sector. This study examines the concept of "happiness" in general and the Islamic practice of Taqwa ("God's consciousness")-comprising Islamic spirituality (IS) and Islamic social responsibility (ISR)-specifically. This empirical study on Pakistan's banking sector attempts to enhance our understanding of how the practice of Taqwa influences employee happiness. The study uses survey data drawn from 500 employees working in nine of Pakistan's highest credit-rated banks. Exploratory factor analysis and confirmatory factor analysis of the main constructs (i.e., IS, ISR, and happiness) are conducted and regression analysis is performed to examine the relationship between Taqwa and employee happiness. The findings suggest that Taqwa, including the practice of IS and ISR, has a positive impact on employee happiness. This study should be useful to those engaged in educational, academic, or organizational management, including anyone pursuing training and human development or policymaking initiatives.
Keywords: I31; M14; Z12; 650; Taqwa; Islamic spirituality; Islamic social responsibility; happiness; God